Indications and complications of colostomy in newborn: our experience - Chanchlani, Roshan; Shrivastava, Dhirendra (International Surgery Journal, 2019)
Background: The aim of the present study was to evaluate the indications, complications and outcome of colostomy in newborn patients. Methods: This is a descriptive, retrospective study carried out in the Department of Pediatric surgery, Gandhi Medical College Bhopal to evaluate acceptance and outcome of colostomy in newborn over a one year period from March 2018 to March 2019. All newborn with diagnosis of anorectal malformation, Hirshsprungs disease and other emergency conditions underwent transverse loop colostomy by expert and trained pediatric surgeon. Results: Out of 40 patients operated complications of colostomy was seen in 18 (45%) patients. Most common complication was skin excoriation in 08 patients (20%), bleeding from stoma site in 02 (05%) cases. Stoma prolapse occurred in 02 (05%) patients. Wound infection, dehiscence, stomal stenosis and parastomal hernia was seen in one patient each 2 (2.5%). 2 (0.5%) patient died due to multiple congenital anomalies. Conclusions: Colostomy in children is associated with significant morbidity in developing country. To minimize these problems, the pediatric surgeon should focus on the management and early closure of a colostomy.